A study on the effectiveness of a participatory self-care model for homebound older adults in Khueang Nai District, Ubon Ratchathani Province, Thailand: 10.55131/jphd/2025/230102 - thongaram, Nopadol; Kanokporn Somporn,; Thassaporn Chusak,; Sutthisak Surirak, (Journal of Public Health and Development, 2024)
Thailand is undergoing a structural social transformation into a complete aging society. This study aimed to investigate the effectiveness of a participatory self-care model for homebound older adults in Khueang Nai District, Ubon Ratchathani Province, Thailand. Given the rapid growth of the older adult population, Thailand faces significant challenges in fostering a quality aging society. Promoting self-care abilities among older adults can mitigate frailty and enhance their quality of life. The study employed a cross-sectional design and a randomized controlled trial (RCT) with pre-post test measurements. The sample comprised 64 homebound older adults aged 60 years and above, divided into an experimental group (n=32) and a control group (n=32). Data were collected through a questionnaire assessing general information, self-care knowledge, health-promoting behaviors, and activities of daily living (ADL). Descriptive statistics and analytical tests (Independent t-test and Paired t-test) were utilized for data analysis. The results indicated that after the four-month implementation of the developed participatory self-care model, the experimental group demonstrated significantly higher mean scores in knowledge, health-promoting behaviors, and ADL compared to the control group (p<0.05). Additionally, the experimental group exhibited significantly lower mean blood pressure and blood sugar levels (p<0.05). However, there was no significant difference in body mass index (BMI) between the groups. These findings suggest that the developed participatory self-care model can effectively enhance health knowledge, behaviors, and daily living abilities while helping to control risk factors for chronic diseases in homebound older adults. This model has the potential to be expanded and applied to older adults’ care in other areas to promote their quality of life and well-being.